Introduction to Skin Biothermomechanics and Thermal Pain - Xu, Feng.; Lu, Tianjian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
"Introduction to Skin Biothermomechanics and Thermal Pain" introduces the study of coupled bio-thermo-mechanical and neural behavior of skin tissue in response to thermal and mechanical loads. The research in this book focuses on the theoretical modeling and experimental investigation of heated skin tissue in order to provide a predictive framework for thermal therapies of diseased tissue in clinics. Furthermore, by developing solution tools, it focuses on changes in treatment parameters leading to more effective therapies. The book is intended for researchers and scientists in Bioengineering, Heat Transfer, Mechanics, Biology and Neurophysiology, as well as clinicians. Dr. Feng Xu is a research fellow at Harvard Medical School, Boston, MA, USA. Dr. Tianjian Lu is a professor at the School of Aerospace, Xi'an Jiaotong University, Xi'an, China. Dr. Xu and Dr. Lu are also affiliated with Biomedical Engineering and Biomechanics Center at Xi'an Jiaotong University, Xi'an, China.
Introduction -- Skin Structure and Blood Flow -- Skin Bioheat Transfer and Thermal Damage -- Analysis of Skin Bioheat Transfer -- Skin Mechanical Behaviour -- Skin Biomechanics Experiments -- Skin Biomechanics Modelling -- Introduction of Skin Biothermomechanics -- Analysis of Skin Biothermomechanics -- Experimental Characterization of Skin Biothermomechanics -- Skin Thermal Pain Mechanism -- Physiological Features of Pain Sensation -- Skin Thermal Pain Modelling.
Keywords: Engineering; Neurology; Biomedical engineering; Engineering; Biomedical Engineering; Biophysics and Biological Physics; Neurology; Engineering Thermodynamics, Heat and Mass Transfer; Transportation